Risk Factors Cannot Be Change In Diabetes Mellitus Disease In Ujung Kubu Health Center - Wahidah Wahidah; Zata Ismah (Pena Cendekia Insani, 2021)
Diabetes mellitus (DM) is a chronic degenerative disease. This study is an analytical observational study with a case-control design that looks at the risk factors for irreversible diabetes mellitus at the Ujung Kubu Health Center in 2020. The population is all patients who have visited the Ujung Kubu Health Center. The sample consisted of 105 control groups and 110 case groups. Sampling technique with total sampling. The type of secondary data belongs to the Ujung Kubu Health Center. It was collecting data by analyzing raw data using a questionnaire. Diabetes mellitus was identified in 55.3% of the family history and relatively common in women 67.4%. The average age of DM patients was 42 years, with blood sugar levels of 184.55 Mg/dl (95% CI 176.27-193.94). DM is still a concern regarding risk factors, especially those that cannot be changed.